The Possibility of Producing Maiolica Glass from Local Materials (The Peerian Journal, 2023)
This paper aims to explore the feasibility of producing basic white glass (Maiolica) from local materials and applying it to the surfaces of pottery bodies made from local clay (AlMahawil clay in Babil Governorate). The current research consists of five chapters. Chapter one presents the research problem as follows: Is it possible to produce Maiolica glass from local materials? The significance and necessity of this research lie in environmental protection by recycling and reusing accumulated palm frond residues to enhance artistic taste and beauty in pottery, besides achieving economic benefits. The research sets the temporal, spatial, and objective boundaries, defines terms, and introduces the theoretical framework in the second chapter. This framework includes understanding the primary materials of glass and its classifications into transparent and opaque glass. Chapter three is allocated to the research procedures, employing an experimental approach. It involves formulating a mixture of palm frond ash with additives based on a specific ratio and subjecting the mixtures to a set standard. Chapter four presents and discusses the findings, including three models representing the research population, where laboratory tests were conducted to measure surface tension, glass density, and texture. Supporting tests, such as microscopic examination, aimed to identify crystalline formations, phases, and unmelted substances